Ultrasound-assisted rapid biological synthesis and characterization of silver nanoparticles using pomelo peel waste. (15th August 2022) - Barbhuiya, Rahul Islam; Singha, Poonam; Asaithambi, Niveditha; Singh, Sushil Kumar
Graphical abstract: Highlights: SNPs were successfully synthesized utilizing pomelo peel extract as a reducing agent, The ultrasound-assisted reduction was faster compared to room temperature reduction. The crystallite size of SNPs was 35 to 40 nm in diameter. Phenolic compounds were able to cap metal ions and reduce them. The SNPs were effective as antibacterial agents against E. coli and B. cereus . Abstract: Synthesis of silver nanoparticles by green route is an emerging technique drawing more attention recently because of several advantages over the conventional chemical ways. The overall objective of the research was focused on the green synthesis of silver nanoparticles using pomelo peel waste via a rapid and eco-friendly ultrasonic-assisted technique and their characterization. Different factors affecting the synthesis, like methodology for the preparation of extract and various treatment conditions for the synthesis, were also studied. The developed nanoparticles were characterized for their optical, molecular, microstructural, and physical properties by UV–visible spectroscopy, dynamic light scattering (DLS), zeta-potential measurements, scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FT-IR). The green synthesized nanoparticles were found almost spherical when treated at room and high temperatures and cubical when treated with ultrasonication. As obtained from the XRD studies, the size of crystallite nanoparticles was 35 to 40 nm in diameter. The EDX, FT-IR, and zeta potential analysis corroborated the role of phenolic compounds in capping and reduction of the metal ion. The capping ability of the polyphenolic component in the extract was used to achieve size stability. The nanoparticles also showed antibacterial activity against gram-negative and gram-positive bacteria, owing to the inherent antibacterial capability of silver nanoparticles.